Tueak Serembeak: The Role of Parenting in Early Character Development and Education - Triani, Lili; Hartati, Sofia; Meilani, R.Sri Martini (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
The challenge of implementing character education has an impact on the development of children's character. This study aims to describe the form of parenting using tueak serembeak in early character development and education in the Rejang tribe. This qualitative research uses a case study method with two male respondents. Data was collected by documentation, interviews, observations, and field notes and analysed using the Miles and Huberman stages. The theoretical study as the basis of research shows that tueak serembeak can form twelve characters in early childhood, responsibility, courage to take decisions, sharing, caring, survival, tenacity, cooperation, hard work, never give up, keep the spirit, dare to accept challenges, and be patient in dealing with problems. However, the findings in the field show that there are only four characters that appear, being responsible, sharing, caring and patient in dealing with problems. Other characters that appear not based on the teachings of tueak serembeakare independent, creative, and friendly characters. This happens because of the influence of external intervention, education in Air Raman Village, which has developed, advanced technology and open community life. A suggestion for further research, is experimental research based on tueak serembeak teachings that can explain more clearly the influence of this teaching on other aspects of child development. Keywords: Early Character Development, Parenting, Tueak Serembeak References: Acar, I. H., Uçuş, Ş., & Yıldız, S. (2017). Parenting and Turkish children’ s behaviour problems: The moderating role of qualities of parent – child relationship moderating role of qualities of parent – child relationship. 4430(September). https://doi.org/10.1080/03004430.2017.1365362 Adhe, K. R. (2014). Penanaman Karakter Anak Usia 5-6 Tahun Pada Masyarakat Samin. Asscheman, J. S., He, J., Koot, S., Buil, J. M., Krabbendam, L., & Lier, P. A. C. Van. (2020). Classroom peer preferences and the development of sharing behavior with friends and others. International Journal of Behavioral Development, 44(5), 412–423. https://doi.org/10.1177/0165025420911094 Bavarian, N., Lewis, K. M., Dubois, D. L., Acock, A., Vuchinich, S., Silverthorn, N., Snyder, F. J., Day, J., Ji, P., & Flay, B. R. (2013). Using social-emotional and character development to improve academic outcomes: A matched-pair, cluster-randomized controlled trial in low-income, urban schools. The Journal of School Health, 83(11), 771–779. PubMed. https://doi.org/10.1111/josh.12093 Berkowitz, R., Astor, R. A., Pineda, D., DePedro, K. T., Weiss, E. L., & Benbenishty, R. (2021). Parental Involvement and Perceptions of School Climate in California. Urban Education, 56(3), 393–423. https://doi.org/10.1177/0042085916685764 Castro-schilo, L., Taylor, Z. E., Ferrer, E., Richard, W., Conger, R. D., Widaman, K. F., Conger, R. D., & Widaman, K. F. (2012). Parenting: Science and Practice Parents’ Optimism, Positive Parenting, and Child Peer Competence in Mexican- Origin Families Parents’ Optimism, Positive Parenting, and Child Peer Competence in Mexican-Origin Families. September 2013, 37–41. https://doi.org/10.1080/15295192.2012.709151 Dalimonte-Merckling, D., & Williams, J. M. (2020). Parenting Styles and Their Effects☆. In J. B. Benson (Ed.), Encyclopedia of Infant and Early Childhood Development (Second Edition) (pp. 470–480). Elsevier. https://doi.org/10.1016/B978-0-12-809324-5.23611-0 Daniel, G. R., Wang, C., & Berthelsen, D. (2016). Early Childhood Research Quarterly Early school-based parent involvement, children’ s self-regulated learning and academic achievement: An Australian longitudinal study. Early Childhood Research Quarterly, 36, 168–177. https://doi.org/10.1016/j.ecresq.2015.12.016 Dea, L. F., Anwar, M. S., & Yusuf, M. (2020). Building Early Childhood Character through KH. Wahid Hasyim Education Model at RA Ma’ arif Metro. 6(2), 109–120. http://dx.doi.org./0.442/al-athfal.2020.62-02 Diana, R. R., Chirzin, M., Bashori, K., Suud, F. M., & Khairunnisa, N. Z. (2021). Parental Engagement on Children Character Education: The Influences of Positive Parenting and Agreeableness Mediated by Religiosity. Jurnal Cakrawala Pendidikan, 40(2), 428–444. https://doi.org/10.21831/cp.v40i2.39477 Ekorusyono, Y., Rosyadi, I., & Tri Bima, P. (2015). Roh kehidupan Suku Rejang. Buku Litera. Freijo, E. B. A., López, M. J. R., Freijo, E. B. A., & López, M. J. R. (2018). Positive parenting in Spain: Introduction to the special issue Positive parenting in Spain: Introduction to the special issue. 4430. https://doi.org/10.1080/03004430.2018.1501565 Gomez, Jessie A; Carter, Alice S; Forbes, Danielle; Gray, S. A. o. (2019). Parental Insightfulness and Parenting Behavior: A two-dimensional analysis of parent contributions to child cognitive outcomes. HHS Public Access, 20(3), 255–271. https://doi.org/10.1080/14616734.2018.1446734.Parental Gü, S. K. (2017). The Education of Developing Responsibility Value *. 5(2), 5–8. https://doi.org/10.11114/jets.v5i2.1361 Hariyanto, S. M. (2012). Konsep dan Model Pendidikan Karakter [Character Education Concepts and Models]. Remaja rosdakarya. Hodijah, S., Rachmawati, Y., Studi, P., Guru, P., Anak, P., Dini, U., Pedagogik, D., Pendidikan, F. I., & Indonesia, U. P. (2018). Upaya Guru Dalam Menanamkan Sifat Sabar Di RA Persis I Kota Bandung. EDUKIDS: Jurnal Pertumbuhan, Perkembangan, Dan Pendidikan Anak Usia Dini, 15(229), 95–102. Kertajaya, H. (2010). Grow With Character, The Model Marketing. PT Gramedia Pustaka Utama. Lee, G. (2013). Programs: Korean Children’ s Experiences Re-emphasizing Character Education in Early Childhood Programs Korean Children’ s Experiences. Childhood Education, October 2014, 37–41. https://doi.org/10.1080/00094056.2013.830907 Listyarti, R. (2012). Pendidikan Karakter dalam Metode Aktif, Inovatif dan Kreatif. Erlangga. Luciano, M., & Visscher, P. M. (2012). Multivariate Genetic Analyses of Cognition and Academic Achievement from Two Population Samples of 174, 000. 699–710. https://doi.org/10.1007/s10519-012-9549-7 Maas, A. J. B. M., Cock, E. S. A. De, Vreeswijk, C. M. J. M., Ad, J. J. M., Bakel, H. J. A. Van, Maas, A. J. B. M., Cock, E. S. A. De, & Vreeswijk, C. M. J. M. (2016). A longitudinal study on the maternal – fetal relationship and postnatal maternal sensitivity. 6838(April). https://doi.org/10.1080/02646838.2015.1112880 McDevitt, T. M., & Ormrod, J. E. (2015). Child Development and Education. Pearson Education. https://books.google.co.id/books?id=h7KgBwAAQBAJ Mei-ju, C., Chen-hsin, Y., & Pin-chen, H. (2014). The Beauty of Character Education on Preschool Children’ s Parent-Child Relationship. Procedia - Social and Behavioral Sciences, 143, 527–533. https://doi.org/10.1016/j.sbspro.2014.07.431 Miles, M. B., Huberman, A. M., & Saldaña, J. (2014). Qualitative data analysis: A methods sourcebook (Third edition). SAGE Publications, Inc. Moleong, L. J. (2010). Metodologi Penelitian Kualitatif. Remaja Rosdakarya. Mulyadi, B. (2020). Early Childhood Character Education in Japan. 07063. https://doi.org/10.1051/e3sconf/202020207063 Musi, M. A., Amal, A., & Hajerah, H. (2015). Pengasuhan Anak Usia Dini Perspektif Nilai Budaya Pada Keluarga Bajo Di Kabupaten Bone [Early Childhood Care Perspective of Cultural Values in Bajo Families in Bone Regency]. 18(1). https://doi.org/10.26858/ijes.v18i1.3601 Paul, S.-A. S., Hart, P., Augustin, L., Clarke, P. J., & Pike, M. (2020). Parents’ perspectives on home-based character education activities. Journal of Family Studies, 1–23. https://doi.org/10.1080/13229400.2020.1806097 Rosyada, A., & Retnomurti, A. B. (2016). The Use of Positive Language on Children Education to Build Children’ s Positive Behaviour. 01(01), 1–8. http://dx.doi.org/10.30998/scope.v1i01.868 Semke, C. A., & Sheridan, S. M. (2011). Family-School Connections in Rural Educational Settings: A Systematic Review of the Empirical Literature. [superscript 2] Working Papers. Research in Rural Education. September, S. J., Rich, E. G., & Roman, N. V. (2016). The role of parenting styles and socio-economic status in parents’ knowledge of child development. Early Child Development and Care, 186(7), 1060–1078. https://doi.org/10.1080/03004430.2015.1076399 Sriwilujeng, D. (2017). Panduan Implementasi Penguatan Pendidikan Karakter [Guidelines for the Implementation of Strengthening Character Education]. Esensi Penerbit Erlangga. Suardani, L., Pudjawan, K., & Tirtayani, L. A. (2016). Perbedaan Tingkat Kemandirian Anak Usia 5-6 Tahun Dilihat Dari Status Pekerjaan Ibu Di Kelurahan Banyuning [Differences in the level of independence of children aged 5-6 years seen from the work status of mothers in Banyuning Village]. Journal Pendidikan Anak Usia Dini Undiksha, 4(2), 12. http://dx.doi.org/10.23887/paud.v4i2.7765 Wang, Zhe; Deater-Deckard, K. (2013). Resilience in Gene-Environment Transactions. In Goldstein S., Brooks R. Handbook of Resilience in Children. Springer, Boston, MA. https://doi.org/10.1007/978-1-4614-3661-4_4 Zong, X., Zhang, L., & Yao, M. (2017). Parental involvement and Chinese elementary students’ achievement goals: The moderating role of parenting style. Educational Studies, 5698(October), 1–16. https://doi.org/10.1080/03055698.2017.1373634